Analisis Perbandingan Kinerja Keuangan Bank Syariah Sebelum dan Sesudah Merger yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 (Jurnal Kendali Akuntansi, 2023)
This study aims to determine differences in company performance seen from the ratio of profitability, liquidity and activities before the merger and to find out the differences in company performance seen from the ratios of profitability, liquidity and activities after the merger. the population consists of Sharia Banking companies listed on the Indonesia Stock Exchange. The total number of companies in this population is 13 entities. The sampling technique uses the purposive sampling method and obtains the results of Islamic banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The population of companies in this study was 4 before the merger and 1 after the merger. Data analysis used comparative analysis and descriptive statistical analysis using SPSS as a testing tool. The results of the study show that there are differences in the average ratio of liquidity and profitability ratios in ROI before the merger. Then there are differences in the profitability ratios on NPM, ROA, and ROE after the merger. Meanwhile, the activity ratio shows no significant difference either before or after the merger.